PELATIHAN PENGENALAN DIRI UNTUK MENINGKATKAN SELF ESTEEM REMAJA DI PANTI ASUHAN AL-HIDAYAH PADANG - Annisa Rahmah Ghaffari; Eni Novita Sari; Nesya Nabilfaizy Albib; Phasya Isyedwina Febriani; Yunda Muliani (PUSAKO : Jurnal Pengabdian Psikologi, 2024)
The orphanage has a population consisting of children of various age ranges who have numerous family problems. Adolescents are one of the common age groups that make up the population living in the orphanage. Most of these teenagers experience alienation, difficulty in channeling negative emotions, or even consider themselves to lack self-assertiveness, and feel like a source of problems for the environment. Therefore, it is necessary to have self awareness, one of which can be achieved through self recognition. The aim of this intervention is to enhance the self-esteem of the teenagers at Al-Hidayah Orphanage in Padang by providing them with knowledge to recognize themselves. The method used involves training the orphanage’s teenagers in self recognition. The training activity lasts for approximately 120 minutes and concludes with the participants making personal commitments.